Ergotamine-Associated Valvulopathy with Recurrent Chylous Pleural Effusion - Bois, John P. (Texas Heart Institute, 2012)
We report a rare case of ergotamine-associated mitral stenosis in a 55-year-old woman who presented with recurrent chylous pleural effusion. Echocardiographic, gross, and microscopic features of the mitral valve were consistent with chronic ergotamine-induced valvulopathy. We conclude that medication-induced valvulopathy should be included in the differential diagnosis of valvular heart disease. In addition, cardiac function should be monitored before and during long-term therapy with ergotamine or ergotamine-derived dopamine agonists.